2021
DOI: 10.1186/s12967-021-02712-w
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with therapeutic anticoagulation is not associated with immunotherapy response in advanced cancer patients

Abstract: Background Recent preclinical data suggest that there may be therapeutic synergy between immune checkpoint blockade and inhibition of the coagulation cascade. Here, we investigate whether patients who received immune checkpoint inhibitors (ICI) and were on concomitant anticoagulation (AC) experienced better treatment outcomes than individuals not on AC.Affiliation: Kindly confirm if corresponding authors affiliation is identified correctly.The corresponding author's affiliation is correct. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
3
11
0
Order By: Relevance
“…This finding was unexpected because randomized trials showed that the application of LMWH and DOACs reduced the risk of VTE in cancer patients and may thus also reduce the risk of VTE-associated mortality [29][30][31]. However, our data are consistent with previous studies and randomized phase III trials [32], which found no association of concomitant AC with prolonged survival in patients with NSCLC [16] or other advanced solid cancer entities [19,21]. Although the cancer-specific risk of VTE in the pre-ICI era was found to be smaller in melanoma patients [33], melanoma patients treated with ICI show similar rates of TEE-and VTE-associated mortality as compared to patients with other advanced cancers [27,34,35], providing a biological rationale for AC therapy [21].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding was unexpected because randomized trials showed that the application of LMWH and DOACs reduced the risk of VTE in cancer patients and may thus also reduce the risk of VTE-associated mortality [29][30][31]. However, our data are consistent with previous studies and randomized phase III trials [32], which found no association of concomitant AC with prolonged survival in patients with NSCLC [16] or other advanced solid cancer entities [19,21]. Although the cancer-specific risk of VTE in the pre-ICI era was found to be smaller in melanoma patients [33], melanoma patients treated with ICI show similar rates of TEE-and VTE-associated mortality as compared to patients with other advanced cancers [27,34,35], providing a biological rationale for AC therapy [21].…”
Section: Discussionsupporting
confidence: 88%
“…Despite the robust preclinical data, these findings have not been translated into the clinical setting. With few exceptions in tumor subtypes, AC, in general, does not appear to be associated with an improved outcome in tumor patients [19,20]. Investigating the role of AC in the outcome of patients with non-small-cell lung cancer (NSCLC) who have received anti-PD-1 or anti-PD-1-ligand (PD-L1) treatment, Nichetti et al found no effect of AC on the progression-free survival (PFS) or overall survival (OS) [16].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…It is of great interest whether this finding can be translated into a clinical setting. However, a recent retrospective study showed no difference in response rates, progression-free or overall survival in patients receiving ICIs and therapeutic anticoagulation compared to patients who were not on anticoagulation [52]. Of note, anticoagulation included in this study was not limited to factor X inhibitors (including dabigatran, rivaroxaban, apixaban, enoxaparin, and warfarin).…”
Section: Survival and Thrombosis In Patients Receiving Immune Checkpoint Inhibitorsmentioning
confidence: 75%
“…Of note, anticoagulation included in this study was not limited to factor X inhibitors (including dabigatran, rivaroxaban, apixaban, enoxaparin, and warfarin). Moreover, the cohort of patients on anticoagulation in the study was significantly older, with poorer performance status, and a higher percentage had lung cancer, all of which were poor prognostic factors [52]. The authors performed a multivariable analysis to adjust for confounders and reached the same conclusions, but residual confounding could be present.…”
Section: Survival and Thrombosis In Patients Receiving Immune Checkpoint Inhibitorsmentioning
confidence: 90%